The Effect of Islamic Work Ethic and Culture to Enhance Productivity of Batik Worker During Pandemic Covid-19 - Susminingsih, Susminingsih; Asytuti, Rinda; Maghfiroh, Wahidatul; Munip, Munip (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This study aims to analyze the influence of Islamic work ethic and Islamic work culture to enhance the productivity of batik workers during the COVID 19 pandemic. This research used a quantitative approach. The population in this study was 955 workers. The samples were selected using purposive and accidental sampling techniques. Determination of sample size in this research using the Slovin formula with a margin error of 5 %. Data collection was done through survey techniques. A total of 282 respondents have answered the questionnaire using Google Forms through WhatsApp. Google forms were chosen because of direct contact restrictions. The score determination on the questionnaire used the Likert scale. The research data was analyzed using multiple linear analysis techniques. The collected data was processed using SPSS software version 21. This study found that Islamic work ethic (X1) does not affect the productivity of batik workers (Y). Islamic work culture (X2) affected the productivity of batik workers (Y). Islamic work ethic (X1) and Islamic work culture (X2) simultaneously to the productivity of batik workers (Y). This study mentioned that during the COVID 19 pandemic the Islamic work ethic and Islamic work culture of batik workers played a small role in work productivity. Penelitian ini bertujuan untuk menganalisis pengaruh etos kerja Islam dan budaya kerja Islam untuk meningkatkan produktivitas pekerja batik selama pandemi COVID-19. Penelitian ini menggunakan pendekatan kuantitatif. Populasi dalam penelitian ini adalah 955 pekerja. Sampel dipilih menggunakan teknik purposive dan accidental sampling. Penentuan ukuran sampel dalam penelitian ini menggunakan rumus Slovin dengan margin error 5%. Pengumpulan data dilakukan melalui teknik survei. Sebanyak 282 responden telah menjawab kuesioner menggunakan google form melalui WhatsApp. Formulir Google dipilih karena pembatasan kontak langsung. Penentuan skor pada kuesioner menggunakan skala Likert. Data penelitian dianalisis menggunakan beberapa teknik analisis linier. Data yang dikumpulkan diproses menggunakan perangkat lunak SPSS versi 21. Studi ini menemukan bahwa etos kerja Islam (X1) tidak mempengaruhi produktivitas pekerja batik (Y). Budaya kerja Islam (X2) mempengaruhi produktivitas pekerja batik (Y). Etos kerja Islam (X1) dan budaya kerja Islam (X2) sekaligus produktivitas pekerja batik (Y). Studi ini menyebutkan bahwa selama pandemi COVID-19 etos kerja Islam dan budaya kerja Islam pekerja batik memainkan peran kecil dalam produktivitas kerja.